Microscopic resection margin status in pancreatic ductal adenocarcinoma – A nationwide analysis. (March 2021) - Daamen, L.A.; van Goor, I.W.J.M.; Schouten, T.J.; Dorland, G.; van Roessel, S.R.; Besselink, M.G.; Bonsing, B.A.; Bosscha, K.; Brosens, L.A.A.; Busch, O.R.; van Dam, R.M.; Fariña Sarasqueta, A.; et al.
Abstract: Introduction: First, this study aimed to assess the prognostic value of different definitions for resection margin status on disease-free survival (DFS) and overall survival (OS) in pancreatic ductal adenocarcinoma (PDAC). Second, preoperative predictors of direct margin involvement were identified. Materials and methods: This nationwide observational cohort study included all patients who underwent upfront PDAC resection (2014–2016), as registered in the prospective Dutch Pancreatic Cancer Audit. Patients were subdivided into three groups: R0 (≥1 mm margin clearance), R1 (<1 mm margin clearance) or R1 (direct margin involvement). Survival was compared using multivariable Cox regression analysis. Logistic regression with baseline variables was performed to identify preoperative predictors of R1 (direct). Results: 595 patients with a median OS of 18 months (IQR 10-32 months) months were analysed. R0 (≥1 mm) was achieved in 277 patients (47%), R1 (<1 mm) in 146 patients (24%) and R1 (direct) in 172 patients (29%). R1 (direct) was associated with a worse OS, as compared with both R0 (≥1 mm) (hazard ratio (HR) 1.35 [95% and confidence interval (CI) 1.08–1.70); P < 0.01) and R1 (<1 mm) (HR 1.29 [95%CI 1.01–1.67]; P < 0.05). No OS difference was found between R0 (≥1 mm) and R1 (<1 mm) (HR 1.05 [95% CI 0.82–1.34]; P = 0.71). Preoperative predictors associated with an increased risk of R1 (direct) included age, male sex, performance score 2–4, and venous or arterial tumour involvement. Conclusion: Resection margin clearance of <1 mm, but without direct margin involvement, does not affect survival, as compared with a margin clearance of ≥1 mm. Given that any vascular tumour involvement on preoperative imaging was associated with an increased risk of R1 (direct) resection with upfront surgery, neoadjuvant therapy might be considered in these patients.